Two-period variability of the intermediate polar FO Aqr - Breus, V.V.; Andronov, I.L.; Hegedus, T.; Dubovsky, P.A.; Kudzej, I. (Advances in Astronomy and Space Physics, 2012)
We present results of CCD photometric study of the intermediate polar FO Aqr based on observations obtained at the Baja Astronomical Observatory, Hungary, and at the Vihorlat Astronomical Observatory, Slovakia. We analysed variability of the spin period of the white dwarf in FO Aqr using our observations and previously published minima timings. The spin period is significantly shorter than before 2000.